A comparative study of lipid profile in smokers and non smokers between 30 to 40 years and prediction of 10 years risk of cardiovascular disease based on Framingham scores - M., Mithun; ., Dhandapani; ., Venkatraman; J., Arun Daniel (International Journal of Advances in Medicine, 2019)
Background: Atherosclerosis has been described as a lipid driven inflammatory disorder of the arterial wall. Smoking is one of the most common modifiable risk factors for atherosclerosis and is the major epidemiological factor in increasing morbidity and mortality of chronic heart diseases (CHD). The objectives of this study were based on to estimate the status of lipid profile in both smokers and non-smokers and compare with each other, to predict the 10 years risk of cardiovascular risk based on Framingham score in smokers and non-smokers. Methods: This retrospective, case-control study was conducted among 50 smokers (cases) and 50 normal individuals (controls) attending to the department of medicine during the period between December 2016 and May 2018. The socio-demographic data and clinical history was obtained using a semi-structured questionnaire and then patients were subjected to blood investigations including estimation of lipid profile by CHOD/PAP method. Results: The mean age of the study participants was 34.7±2.9 years. The duration of smoking among the smokers was 5.4±2.9 years on an average. There was a significant increase in serum cholesterol levels (245.6±39.8 versus 155.8±15.2 mg/dl), serum triglycerides (217.3±42.2mg/dl versus 127.4±10.6), LDL (171.1±35.2 versus 85.7±15.1 mg/dl) and VLDL (43.5±10.5 versus 15.3±5.5mg/dl) among the smokers versus non-smokers. There was a significant (p<0.001) decrease in HDL levels among the smokers (30.8±3.4 mg/dl) when compared with the non-smokers (44.8±5.3 mg/dl). There was a highly significant difference between Framingham risk scores of smokers and non-smokers. Conclusions: The study established that the lipid profile was deranged towards atherogenesis among the smokers when compared to the non-smokers which was reflected in the significant increase in risk as calculated by Framingham risk score.